HUBUNGAN ANTARA PAPARAN ASAP ROKOK DAN FREKUENSI TERJADINYA EKSASERBASI ASMA PADA PASIEN ASMA YANG BEROBAT KE RSU DR SOEDARSO - ., Prayogi Agil (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background: The number of asthma patients in the world is still high. Indonesia was on 6th in the world for the most male smoker. High number of active smoker in Indoseia caused high number of passive smoker. There isnt many research about the relationship of asthma and second-hand smoke exposure in adult.Objective: The aim of this research was to find out about the relationship between second-hand smoke exposure and frequency of asthma exacerbation on asthma patients treated in RSU dr. Soedarso.Method: This research was an analytic observational study with cross sectional approach. Data were collected on May 2012 in outpatient clinic and inpatient unit of lung division dr. Soedarso general hospital. Patients were asessed with Asthma Control Test (ACT) to assessed their asthma control level before asessed for second-hand smoke exposure and frequency of asthma exacerbation they had.Result: There is 29 patients (72,5%) with moderate exposure and 11 patients (27,5%) with high exposure. There is a significant relationship (p = 0,031) between the longer duration patients is exposed by second-hand smoke and more frequent asthma exacerbation on patients treated in RSU dr. Soedarso.Conclusion: The longer the patients was exposed to second-hand smoke, the higher the frequency of asthma exacerbation in asthma patients treated in dr. Soedarso general hospital.Keyword: Asthma exacerbation, second-hand smoke exposure